2021
DOI: 10.3390/su13169456
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Watershed Using Remote Sensing and Geographic Information System

Abstract: Soil erosion is becoming a major concern at the watershed scale for the environment, natural resources, and sustainable resource management. Therefore, the estimation of soil loss through this phenomenon and the identification of critical soil erosion-prone areas are considered to be key tasks in the soil conservation programme for the design and implementation of best management practices for specific regions or areas. In the present study, revised universal soil loss equation (RUSLE) modelling is combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Another study performed in lower Sutlej sub-basin of Punjab, India showed that about 94.4 % and 4.7 % of the total area suffered from very slight erosion (0-5 tonne/hectare/year) and slight erosion (5-10 tonne/hectare/year), respectively, whereas 0.11 % area experienced very severe soil loss (> 25 tonne/hectare/year) that is very similar to the present study (Sharma et al, 2022). A new study performed using a revised universal soil loss equation method in Nainital district, Uttarakhand, India revealed the annual average soil loss ranged between 20 to 80 tonne/hectare/year in the study area which has a similarity with the present result (Kumar et al, 2021). A study conducted in the Banas basin of Rajasthan of India reflects that 90 % area has under 0-10 tonne/hectare/year soil loss category (Singh et al, 2023).…”
Section: Fig 7: Soil Loss Mapsupporting
confidence: 88%
“…Another study performed in lower Sutlej sub-basin of Punjab, India showed that about 94.4 % and 4.7 % of the total area suffered from very slight erosion (0-5 tonne/hectare/year) and slight erosion (5-10 tonne/hectare/year), respectively, whereas 0.11 % area experienced very severe soil loss (> 25 tonne/hectare/year) that is very similar to the present study (Sharma et al, 2022). A new study performed using a revised universal soil loss equation method in Nainital district, Uttarakhand, India revealed the annual average soil loss ranged between 20 to 80 tonne/hectare/year in the study area which has a similarity with the present result (Kumar et al, 2021). A study conducted in the Banas basin of Rajasthan of India reflects that 90 % area has under 0-10 tonne/hectare/year soil loss category (Singh et al, 2023).…”
Section: Fig 7: Soil Loss Mapsupporting
confidence: 88%
“…Watersheds are one of the best spatial systems for managing water and soil resources (Gajbhiye et al 2013;Kumar et al 2021) which for better management of this system is divided into homogeneous hydrological units or SWs (Aher et al 2014;Lin et al 2020). The effects of SWs on each other can be more important in FGP (Avand et al 2021), which shows the importance of prioritizing SWs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed a number of issues with data quality, classi er accuracy and data validation. Additionally, it appears from the literature that no research has been done to look into changes in LU/LC patterns and their prediction in the study area [20].Finally, machine learning Random Forest classi er is used to get high accuracy. The results of the study are used to identify the critical elements that affect LU/LC dynamics and improve land use policy for sustainable land use planning and development.…”
Section: Introductionmentioning
confidence: 99%